A Study on the Effect of Imported Wheat Prices on Türkiye’s Pasta Exports: ARDL Approach - Sarihan , Ahmed Yusuf (Ekonomika, 2024)
Türkiye has possessed significant agricultural opportunities throughout its history. Although the effective utilization of these opportunities is a subject of debate today, the country still plays a significant role in the global trade of some agricultural products. When discussions about Türkiye’s exports are examined, a common complaint is the external dependency of the export industry. However, there are also debates about the diminishing agricultural advantages that have been present since the past. When these discussions are brought together, the trade of certain processed agricultural products, whose raw materials are agricultural products, also becomes a noteworthy research topic due to a similar import dependency. In this study, an analysis was conducted using time series and the ARDL model to investigate whether there is a relationship between Türkiye’s pasta export quantity, as one of the leading pasta exporter’s globally, and the prices of wheat imports from Ukraine, Russia, and Bulgaria. Also robustness checks enhanced the analyzes by employing FMOLS and DOLS methods. The research findings indicate variations in the impact of wheat prices from country to country on the quantity of pasta exported by Türkiye. Recommendations regarding the importance of wheat production in Türkiye are also provided as a result of the research.